Assessing EFL Students’ Translation Competence in Argumentative Texts: An Analysis of Accuracy, Acceptability, and Readability - Natsir, Ratu Yulianti; Baso, Farisha Andi (JOLLT Journal of Languages and Language Teaching, 2026)
This study investigates the translation competence of third-semester students in the English Education Program at Universitas Muhammadiyah Makassar, focusing on the translation of argumentative texts from English into Indonesian. While previous research has mainly examined narrative or descriptive genres, studies on argumentative texts remain limited, despite their prominence in academic contexts and their demanding linguistic and cognitive features. This study addresses the lack of empirical work on argumentative translation and contributes practical strategies for EFL teachers. A quantitative descriptive design was employed to evaluate students’ translation performance across three key dimensions: accuracy, acceptability, and readability. Data were collected through a performance-based translation test and assessed using a rubric adapted from Nababan (2012). Findings revealed that although most students produced translations that were acceptable and readable, accuracy emerged as the most problematic dimension. Only 53.3% of the students achieved fully accurate translations, compared with stronger performance in acceptability (66.7%) and moderate results in readability (40%). These outcomes indicate that while students demonstrated cultural and linguistic fluency, they struggled with semantic precision and logical coherence. The results highlight the pedagogical need for integrating genre-based translation tasks into EFL curricula and providing explicit instruction in strategies such as managing logical flow, coherence, and stylistic alignment.